Size-controlled hydroxyapatite particle nucleation in natural rubber latex membranes - Piazza, Rodolfo Debone [UNESP] (2025)
Bone regeneration effectively treats fractures, but factors such as injury severity and age can delay healing. In these cases, implants or bone transplants may be required for repair. This study employed the biomimetic approach to fabricate composite membranes for bone tissue engineering. The inherent stretchability, barrier properties, and angiogenic potential of natural rubber latex were integrated with the excellent osteoconductive and osseointegrative properties of hydroxyapatite (HA). By controlling the biomimetic incubation, size-controlled CaP nucleation and growth within the latex matrix were achieved, ranging from nano to micro-scale. Characterization confirmed the successful formation of CaP-latex composites with enhanced surface roughness and wettability. Finally, the cytotoxicity analysis in fibroblasts showed that the Latex_CaP membranes were non-toxic. This combination of material properties offers significant potential for the development of advanced bone grafts with improved bioactivity and enhanced tissue regeneration.